Al-Qur'an ANALISIS HUBUNGAN PEMBELAJARAN TAHFIDZ AL-QUR'AN ‎DENGAN PERKEMBANGAN MORAL SISWA DI SD IT TAHFIDZ ‎AL-MAKKI PEKANBARU: HUBUNGAN PEMBELAJARAN TAHFIDZ AL-QUR'AN DENGAN ‎PERKEMBANGAN MORAL SISWA - Zaharah, Futri; Salsabila, Faarah; Yuni, Rahma; Wildatul Khairia; Sakban, Sakban (EDUPEDIA Publisher, 2025)
This study aims to investigate the relationship between the learning process of tahfidz Al-Qur'an and the improvement of students' moral values at SD IT Tahfidz Al-Makki Pekanbaru. The importance of the influence of religious education on the character and moral formation of students cannot be underestimated. In this research, a qualitative approach focused on case studies is used. This will involve in-depth interviews with teachers, students, and parents, as well as direct observation to obtain accurate and in-depth data. This study shows that the tahfidz learning process has a favorable impact in students' moral growth, which is reflected in the improvement of values such as honesty, discipline, and social care. Through tahfidz learning and the reinforcement of religious values in daily life, the process of students' character building is presented. A more in-depth discussion emphasizes the significance of cooperation between teachers, parents, and the school environment in strengthening moral values. This research shows that the teaching of tahfidz Al-Qur'an has a great influence in shaping the moral character of students at Al-Makki IT Tahfidz Elementary School. It is hoped that this research can be a motivation to design an educational curriculum based on religious values.